1998
DOI: 10.1021/bi981034a
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Peptide Substrates for Mucin-Type O-Glycosylation

Abstract: The structures of three nine-residue peptide substrates that show differential kinetics of O-linked glycosylation catalyzed by distinct recombinant uridine diphosphate-N-acetylgalactosamine:polypeptide N-acetylgalactosaminyltransferases (GalNAc transferases) were investigated by NMR spectroscopy. A combined use of NMR data, molecular modeling techniques, and kinetic data may explain some structural features required for O-glycosylation of these substrates by two GalNAc transferases, GalNAc-T1 and GalNAc-T3. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…The lack of a strong correlation for Thr may be the result of the relatively high and more uniform glycosylation of Thr residues by GalNAc relative to Ser. This is consistent with most in vitro studies showing that Thr residues are typically an order of magnitude more readily glycosylated compared with Ser (11,(17)(18)(19)(20)(21). Note that in Fig.…”
Section: Psm Oligosaccharide Characterization-the Possiblesupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of a strong correlation for Thr may be the result of the relatively high and more uniform glycosylation of Thr residues by GalNAc relative to Ser. This is consistent with most in vitro studies showing that Thr residues are typically an order of magnitude more readily glycosylated compared with Ser (11,(17)(18)(19)(20)(21). Note that in Fig.…”
Section: Psm Oligosaccharide Characterization-the Possiblesupporting
confidence: 90%
“…1 To date, 10 ppGalNAc transferase isoforms have been described (9 -16). Although each transferase has not been fully characterized, their peptide substrate specificities vary within the family (11,(17)(18)(19)(20)(21); many show sensitivity to prior glycosylation, and others require prior addition of GalNAc for activity (9,14,20,(22)(23)(24). The expression of ppGalNAc transferase isoforms with different peptide and/or glycopeptide specificities therefore represents the first step in the regulation of O-glycan structure by peptide sequence in vivo.…”
mentioning
confidence: 99%
“…It has also been reported that the initial O-glycosylation of a peptide substrate influences the subsequent glycosylation, probably due to conformational change of the peptide and the accessibility of pp-GalNAc-Ts for particular acceptor sites (57). There are two consecutive Ser and Thr residues, such as Ser-3/Thr-4 and Ser-11/Thr-12, in HRP.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking glycosylation at T1255A might influence subsequent glycosylation events by inducing conformational changes in the peptide backbone and altering the accessibility of particular glycosylation sites for N-acetylgalactosaminyltransferases. [47][48][49] However, to date it has not been possible to ascertain whether mutation of a given OLG site of VWF affects glycosylation of nearby residues.…”
Section: Org Frommentioning
confidence: 99%
“…Blocking glycosylation at T1255A might influence subsequent glycosylation events by inducing conformational changes in the peptide backbone and altering the accessibility of particular glycosylation sites for N-acetylgalactosaminyltransferases. [47][48][49] However, to date it has not been possible to ascertain whether mutation of a given OLG site of VWF affects glycosylation of nearby residues.Together, the presented data support the hypothesis that OLG(s) present in the hinge, linker region connecting the D3-A1 domains, modulates VWF-platelet interaction both in the presence of ristocetin and shear stress. Importantly, however, the effect of the OLGs seems to be mediated by altering accessibility of the A1 domain in these conditions rather than by an effect on VWF A1-GPIb␣ bond.…”
mentioning
confidence: 99%